Employer Branding in B2B and B2C Companies in India: A Qualitative Perspective. (June 2018) - Biswas, Mukesh K.; Suar, Damodar
The employer branding (EB) phenomenon has garnered the attention of practitioners and academicians over the past decade. However, the subjective experiences of managers on EB are hardly tapped. This study explores company executives' views on EB through the case study method with semi-structured interviews in the context of the business-to-business (B2B) and business-to-consumer (B2C) companies located in India. Four key categories relevant to EB emerged from the data. These are (a) essence of a successful EB, (b) precursors of EB, (c) visibility of the employer and (d) outcomes of EB. Attributes of these categories were explored along the sub-themes, which reveal the respondents' perceptions regarding their implementation of EB strategy. These attributes were similar in B2B and B2C companies.